E-016 The utility of quantitative mra in the detection of cerebral vasospasm after subarachnoid hemorrhage. (23rd July 2022) - Shah, K; White, T; Turpin, J; Teron, I; Woo, H
Abstract : Introduction/Purpose: Aneurysmal subarachnoid hemorrhage (SAH) is a devastating condition often complicated by cerebral vasospasm in the days following the initial event. Non-invasive imaging modalities, such as CT angiography and transcranial Doppler, are commonly employed to detect cerebral vasospasm. However, these screening modalities have inherent limitations and may fail to identify hemodynamic compromise in some patients. Quantitative MRA (qMRA) provides direct measurements of cerebral blood flow and may permit a more clinically relevant assessment of ischemia secondary to cerebral vasospasm. We conducted this preliminary study to evaluate the utility of qMRA in the assessment of cerebral vasospasm after SAH. Materials and Methods: We performed a retrospective analysis of a prospectively maintained database of all patients admitted with subarachnoid hemorrhage who underwent a qMRA between post-bleed day 0 and post-bleed day 21. Volumetric flow rates of the A2, M1, and P2 arteries were assessed on qMRA and compared with vessel diameters on catheter-based angiography performed within 24 hours. The sensitivity, specificity, positive predictive value, and negative predictive value of qMRA for detecting cerebral vasospasm was determined by receiver operator characteristic (ROC) curves. Spearman correlation coefficients were calculated for qMRA flow vs. angiographic vessel diameter. Angiographic vasospasm (VS) was defined as a reduction of the diameter of the vessel by greater than 25% between the baseline cerebral angiogram (obtained at the time of the index procedure) and the follow-up cerebral angiogram. Results: Ten patients with 60 vessels were evaluated with qMRA and catheter-based angiography. The median qMRA flow of all vessels found to have angiographic VS (53 mL/min, IQR 34 mL/min) was significantly lower than the median qMRA flow of vessels without angiographic VS (73 mL/min, IQR 52 mL/min) (p = 0.003). Angiographic VS reduced qMRA flows by 23 ± 5 mL/min in the ACA (p = 0.018), 95 ± 12 mL/min in the MCA (p = 0.042), and 16 ± 4 mL/min in the PCA (p = 0.153) between the baseline qMRA and spasm period qMRA. Two conditions were modeled using ROC curves based on cutoff points of angiographic VS: greater than 25% and greater than 50%. The overall performance of the two models (AUC) was 0.8325 and 0.8267 for angiographic VS >25% and angiographic VS >50%, respectively. The sensitivity, specificity, positive predictive value, and negative predictive value of qMRA for the discrimination of cerebral vasospasm was 84%, 72%, 84%, and 72%, respectively, for angiographic VS >25% and 91%, 60%, 87%, and 69%, respectively, for angiographic VS >50%. The result of the Spearman correlation indicated a significant association between qMRA flows and vessel diameters (R = 0.71, p < 0.001). This correlation was further increased when individualized baseline qMRA flows were included (R = 0.83, p < 0.001). Conclusion: Reduction in qMRA flow is a reliable indicator of angiographic vessel narrowing after SAH and may be useful as a non-invasive imaging modality for the detection of cerebral vasospasm. Disclosures: K. Shah: None. T. White: None. J. Turpin: None. I. Teron: None. H. Woo: None.